A counterfactual analysis of the effects of climate change on the natural interest rate - Jair Neftali Ojeda Joya (Graduate Institute of International and Development Studies, 2022)
Climate change will potentially bring about important macroeconomic effects for all countries in the world and especially for emerging economies. I perform a counterfactual analysis to estimate the potential effect of global warming on the natural interest rate using a state-space semi-structural model of inflation and output determination. The model is estimated with quarterly data for Colombia for the period 1994-2019. I simulate gradual warming of 1êC during this period and include its potential effect on GDP growth and inflation according to recent cross-country estimations in the literature. The estimation with counterfactual data shows that the counterfactual natural interest rate decreases more rapidly to reach near 0% at the end of the period. This result is induced by the persistently negative effects of higher temperatures on trend output growth.
Keywords: E43; E52; Q51; 330; Natural Interest Rate; Climate Change; Monetary Policy; Kalman filter